In the name of the family: The effect of CEO clan culture background on firm internationalization - Liu, Feifei; He, Xinming; Wang, Tao (Journal of business research, 2023)
•CEO clan culture background is positively related to the firm’s degree of internationalization.•The imprint effect is strengthened when the CEO works locally.•The imprint effect is strengthened when facing more intensive competition in the domestic market.•The degree of economic policy uncertainty at home weakens the imprint effect. Clan culture is a traditional culture that is widespread in Asian countries, yet little is known about its impact on crucial firm decisions, such as internationalization. Drawing on upper echelons theory and imprinting theory, we suggest that a CEO’s clan culture background impacts firm internationalization through the mechanism of imprinting and strengthening the individual value of long-term orientation, and that this effect is subject to three conditional factors. Using a unique database of Chinese publicly listed firms, we confirm that (1) CEO clan culture background is positively related to the firm’s degree of internationalization, and (2) the imprint effect is strengthened when the CEO works locally or when the domestic market competition is intensive, but is mitigated when the economic policy at home is unpredictable. Finally, implications and limitations also are discussed.